Médicis daughter : a novel of Marguerite de Valois - Perinot, Sophie (Thomas Dunne Books/St. Martin's Press, 2015)
"Winter, 1564. Beautiful young Princess Margot is summoned to the court of France, where nothing is what it seems and a wrong word can lead to ruin. Known across Europe as Madame la Serpente, Margot's intimidating mother, Queen Catherine de Médicis, is a powerful force in a country devastated by religious war. Among the crafty nobility of the royal court, Margot learns the intriguing and unspoken rules she must live by to please her poisonous family. Eager to be an obedient daughter, Margot accepts her role as a marriage pawn, even as she is charmed by the powerful, charismatic Duc de Guise. Though Margot's heart belongs to Guise, her hand will be offered to Henri of Navarre, a Huguenot leader and a notorious heretic looking to seal a tenuous truce. But the promised peace is a mirage: her mother's schemes are endless, and her brothers plot vengeance in the streets of Paris. When Margot's wedding devolves into the bloodshed of the St. Bartholomew's Day Massacre, she will be forced to choose between her family and her soul. Médicis Daughter is historical fiction at its finest, weaving a unique coming-of-age story and a forbidden love with one of the most dramatic and violent events in French history"--